Antioxidant and anti-inflammatory effects of intravenously injected adipose derived mesenchymal stem cells in dogs with acute spinal cord injury. Issue 1 (December 2015) - Kim, Yongsun; Jo, Sung-ho; Kim, Wan; Kweon, Oh-Kyeong
Abstract Introduction Mesenchymal stem cells can potentially be used in therapy for spinal cord injury (SCI). Methylprednisolone sodium succinate (MPSS) has been used as a scavenging agent in acute SCI treatment, but its use no longer recommended. This study aimed to identify ways to reduce the usage and risk of high doses of glucocorticoid steroids, and determine whether AD-MSCs could be used as an early alternative treatment modality for acute SCI. Methods Sixteen adult beagle dogs with SCI were assigned to four treatment groups: control, MPSS, AD-MSCs, and AD-MSCs + MPSS. Additionally, one dog was used to evaluate the distribution of AD-MSCs in the body after injection. AD-MSCs (1 × 107 cells) were injected intravenously once a day for 3 days beginning at 6 hours post-SCI. MPSS was also injected intravenously according to the standard protocol for acute SCI. A revised Tarlov scale was used to evaluate hindlimb functional recovery. The levels of markers for oxidative metabolism (3-nitrotyrosine, 4-hydroxynonenal, and protein carbonyl) and inflammation (cyclooxygenase-2, interleukin-6, and tumor necrosis factor-α) were also measured. Results At 7 days post-treatment, hindlimb movement had improved in the AD-MSCs and AD-MSCs + MPSS groups; however, subjects in the groups treated with MPSS exhibited gastrointestinal hemorrhages. Hematoxylin and eosin staining revealed fewer hemorrhages and lesser microglial infiltration in the AD-MSCs group. The green fluorescent protein-expressing AD-MSCs were clearly detected in the lung, spleen, and injured spinal cord; however, these cells were not detected in the liver and un-injured spinal cord. Levels of 3-nitrotyrosine were decreased in the MPSS and AD-MSCs + MPSS groups; 4-hydroxynenonal and cyclooxygenase-2 levels were decreased in all treatment groups; and interleukin-6, tumor necrosis factor-α, and phosphorylated-signal transducer and activator transcription 3 levels were decreased in the AD-MSCs and AD-MSCs + MPSS groups. Conclusion Our results suggest that early intravenous injection of AD-MSCs after acute SCI may prevent further damage through enhancement of antioxidative and anti-inflammatory mechanisms, without inducing adverse effects. Additionally, this treatment could also be used as an alternative intravenous treatment modality for acute SCI.